A long-term population study of the Eurasian griffon (Gyps fulvus) in Serbia before and following the establishment of a supplementary feeding program. Issue 2 (4th March 2021) - Marinković, Saša; Hribšek, Irena; Tatalović, Nikola; Skorić, Stefan
Abstract : The Eurasian griffon population in Serbia declined throughout the 20th century from widespread to a rare species, counting a total of 14 detected pairs in two colonies in western Serbia in the 1990s. Although the conservation measures have been implemented since the 1970s, they have had little effect on the further population decline until the supplementary feeding program started in 1989. In this paper, we present the results related to the population trends and reproduction parameters, following the establishment of a supplementary feeding program of the Eurasian griffon in Serbia based on a 34-year survey (1985–2018). By 2018, a total of 2458 tons of supplementary food was provided at three feeding stations. The population increased from 14 detected pairs in two colonies in 1992 to 262 detected pairs in four colonies in 2018. A total of 1807 juveniles were fledged, with breeding success – fledged chicks/laying pairs (i.e., breeding pairs) (0.81 ± 0.07; mean ± SD) and productivity – fledged chicks/detected pairs (0.57 ± 0.10). The amount of supplementary food was in a significant positive correlation with the number of detected and breeding pairs and the number of fledged juveniles. Furthermore, breeding parameters remained high despite the substantial increase in population size, implying that the population is far from saturation level. Our study emphasizes the importance of applied protection measures, especially supplementary feeding. The implementation of appropriate networks of feeding stations and the promotion of free-range livestock farming, as well as returning to the traditional way of disposing of dead cattle, would be a recommendation for future main conservation activities for the Eurasian griffon population in Serbia.